Pendekatan seni interaktif dalam karya seni - Catherine Burai, ak. Ambang. (Universiti Malaysia Sarawak (UNIMAS), 2006)
The development of interactive art in our country is not encouraging compare to other part of the world such as America and Europe. Recently, technology and art able to immerse. It happen to be important to one and other. Interaction in art through the used of technology able to increase the relation between human and the creativity process.